2013
DOI: 10.4049/jimmunol.1300945
|View full text |Cite
|
Sign up to set email alerts
|

The CD226/CD155 Interaction Regulates the Proinflammatory (Th1/Th17)/Anti-Inflammatory (Th2) Balance in Humans

Abstract: CD226 costimulatory signals strongly promote Th1 differentiation, enhancing IFN-γ production by naive T cells. We recently reported that knockdown of CD226 on human T cells resulted in a decrease in T-bet and IFN-γ expression. However, the role of CD226 on Th2 and Th17 cells remains unknown. In this study, we found that CD226 and its ligand CD155 were decreased on Th2-polarized naive T cells, whereas both were highly expressed under Th17 conditions. Most IFN-γ– and IL-17–producing cells expressed high levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
88
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 29 publications
7
88
1
Order By: Relevance
“…We previously demonstrated that DNAM-1, which is a counterreceptor for CD155 and is expressed also on CD4 + T cells, mediates an activating signal for Th1 development in naive CD4 + T cells in human (30). In agreement with this context, Lozano et al (34) suggested that DNAM-1 on CD4 + naive T cells mediates an activating signal for Th1/Th17 differentiation as a result of ligation with CD155. In sharp contrast, the present study demonstrated that CD155 itself mediates a costimulatory signal in CD4 + T cells that promotes Th1 development.…”
Section: Discussionmentioning
confidence: 63%
“…We previously demonstrated that DNAM-1, which is a counterreceptor for CD155 and is expressed also on CD4 + T cells, mediates an activating signal for Th1 development in naive CD4 + T cells in human (30). In agreement with this context, Lozano et al (34) suggested that DNAM-1 on CD4 + naive T cells mediates an activating signal for Th1/Th17 differentiation as a result of ligation with CD155. In sharp contrast, the present study demonstrated that CD155 itself mediates a costimulatory signal in CD4 + T cells that promotes Th1 development.…”
Section: Discussionmentioning
confidence: 63%
“…Blocking of the CD155-TIGIT interaction led, apart from dampening Tigit expression, to enhanced CD226 expression. A recent study described CD226/ CD155 interaction on the T cell surface to be Th2 suppressing, as it downregulates IL-4, IL-13 levels, and GATA3 expression in human nonpolarized T cells via enhancement of Th1 and Th17 responses (42). Thus, in our setting, if activation of CD226 by CD155 was inhibitory for Th2 responses, then blockade of either of these molecules would lead to Th2 enhancement.…”
Section: Il-4-and Il-13-secreting Cd4mentioning
confidence: 61%
“…Thus, it is unlikely that interaction of CD226 with CD155 could restrain Th2 responses in our setting. Supportively, a previous study reported that Th2 differentiation was not regulated through CD226 stimulation (43), and importantly, CD226 blockade had no effect on Th2 polarization (42).…”
Section: Il-4-and Il-13-secreting Cd4mentioning
confidence: 73%
“…It has now become clear that this receptor has broader implications than originally thought in controlling NK cell and T cell function (20,21). CD226 has been implicated in immunological synapse formation (22), T cell proliferation and differentiation (23), and cytokine secretion (21,24). Interestingly, CD112 and CD155 are often present at the surface of malignant PCs in MM patients, and CD226 strongly contributes to NK cell-mediated killing of MM cells in vitro (8,9).…”
Section: Introductionmentioning
confidence: 99%